1992
DOI: 10.1002/adma.19920040316
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles from biodegradable polymers

Abstract: MATERIALSdifference is thus as high as a factor of 3.5. Only when the conversion is higher than 85-90%, does the level of crosslinking agent drastically increase to more than 1 %.If the amount of cross-linking agent is adjusted so that the polymer chains are optimally cross-linked a t low conversions, the cross-linking density may be insufficient, or too high, for the short polymer chains at the end of the reaction. Larger or smaller quantities of cross-linking agent may indeed provide the necessary amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Polymeric nano/microparticles (NP/MPs) have been extensively investigated, especially biodegradable materials, such as chitosan, poly­(lactic acid) (PLA) and poly­( d , L -lactic- co -glycolic) acid (PLGA). These particles are used in the cosmetics industry, diagnostic imaging, tissue engineering, separations and purification of biological product, drug delivery, and as vaccine adjuvants. Previous studies by others have shown that biodegradable particles have a high biosafety and biocompatibility and are able to control the release rate and duration of entrapped cargoes. They can also function as potent vaccine adjuvants, owe to their abilities to improve antigen uptake by antigen-presenting cells (APCs), and further promote the expression of costimulatory molecules and major histocompatibility complex (MHC) molecules. , These excellent properties would be extremely beneficial for various new vaccines, such as protein subunits, recombinant proteins, and synthetic oligopeptides, which have been brought about with the development of biotechnology and genetic engineering . While the antigens we use today have great safety, the weak immunogenicity makes them require adjuvant to elicit powerful humoral and cellular immune response for preventing infectious diseases …”
Section: Introductionmentioning
confidence: 99%
“…Polymeric nano/microparticles (NP/MPs) have been extensively investigated, especially biodegradable materials, such as chitosan, poly­(lactic acid) (PLA) and poly­( d , L -lactic- co -glycolic) acid (PLGA). These particles are used in the cosmetics industry, diagnostic imaging, tissue engineering, separations and purification of biological product, drug delivery, and as vaccine adjuvants. Previous studies by others have shown that biodegradable particles have a high biosafety and biocompatibility and are able to control the release rate and duration of entrapped cargoes. They can also function as potent vaccine adjuvants, owe to their abilities to improve antigen uptake by antigen-presenting cells (APCs), and further promote the expression of costimulatory molecules and major histocompatibility complex (MHC) molecules. , These excellent properties would be extremely beneficial for various new vaccines, such as protein subunits, recombinant proteins, and synthetic oligopeptides, which have been brought about with the development of biotechnology and genetic engineering . While the antigens we use today have great safety, the weak immunogenicity makes them require adjuvant to elicit powerful humoral and cellular immune response for preventing infectious diseases …”
Section: Introductionmentioning
confidence: 99%
“…Tartaric acid is an inexpensive natural resource and a variety of polymers are derived from it such as polyesters, polyamides, poly(ester amide)s and polycarbonates etc. The tartaric acid based polyesters can be potential candidates in controlled drug delivery applications as controlled release agents and drug carriers . More recently, El‐Laboudy et al .…”
Section: Introductionmentioning
confidence: 99%
“…Budući da je period njihove degradacije uglavnom veoma dug, veliki dio istraživačkog interesa je usmjeren ka dobijanju modifikovanih prirodnih polimera. Jedan od načina modifikacije prirodnih polimera je dodavanjem polarnih grupa koje su nestabilnije i pospješuju degradaciju polimera (23).…”
Section: Biodegradabilni Polimeri I Njihova Primjena U Medicini I Farunclassified